CURRENT ADVANCE DIRECTIVE USE IN SOUTH AUSTRALIA: RESULTS FROM THE 2012 SPRING SOUTH AUSTRALIAN HEALTH OMNIBUS SURVEY. Issue 2 (1st June 2013) - Bradley, S L; Woodman, R J; Phillips, P A; Tieman, J
Abstract : Background: Advance directives enable autonomous decision-making for future healthcare and welfare and are an integral part of many advance care planning programmes. Current evidence of use of these instruments in South Australia (SA) is presented. Aim: To ascertain the prevalence and type of advance directives used in SA. Methods: Questions exploring the prevalence and type of advance directives experienced by the South Australian public were submitted to the Spring South Australian Health Omnibus Survey (HOS) 2012. The HOS has been conducted regularly since 1991 and is used by government and nongovernment organisations to assess the healthcare needs of the South Australian community. The survey comprised a random sample of 3055 members of the public drawn in a multi-stage, systematic sampling technique*. Results: Analysis of an unweighted sample of 3055 participants showed that 40% had not completed any advance directive and that 27% have no interest in learning about advance directives. Age and other demographic factors were indicative of differences in participation rates. Discussion: Using the HOS survey enabled analysis of demographic and sociological characteristics of the SA public with prevalence and type of advance directives experienced and provided evidence-based knowledge of the public's engagement in autonomous decision-making for future healthcare and welfare. Conclusion: Accurate ascertainment of the South Australian public's current levels of knowledge and engagement with advance directives can assist future advance care planning initiatives in South Australia as well as provide a basis for further research designed to enhance completion rates of these instruments by the general public.